Strengthening Students' Independent Character in Online Learning Through ASSA C-13-Based M-Modules - Riful Hamidah (Pinisi Journal of Education and Management, 2022)
This study aims to determine the impact of using a mobile module based on ASSA C-13 on strengthening students' independent character in online learning. The stages of the activities are socialization, independent working, collaboration, and exhibition. Data were collected true observations and questionnaires and then are analyzed by descriptive qualitative. The research findings indicate that the learning activities and the level of student independence are in the very good category. Students work on assignments independently and collect them according to the schedule as much as 98%. The independent character of students can still be strengthened even though they study online. This ASSA C-13-based m-module can be recommended in distance learning with online mode.